Efficacy and enactment of variable speed drive in various electrical induction motor application - Thanabal, Navamani (2023)
A single or three-phase induction motor is a common driven mechanical machine in many industrial applications. This electrical drive machine is one of the highest energy consuming machines among others electrical machinery. The induction motor only delivers rated full speed when it is connected directly to the oldest AC motor drivers. However, most applications in current industries need speed control of induction motor to accomplish desire output for the system and reduce the energy waste. Variable speed drive is the most simple and cost-efficient device to control speed of induction motor. Although many research and studies presented on variable speed drive performance and efficiency, in this paper experimental results of electrical unit such as voltage, current and speed on different frequencies with different AC controller which show motor speed varying according to frequency and large of energy saving to accomplish. The simulation of induction motor with conventional motor starter and with variable speed/frequency drive was enacted to determine the performance and efficiency of electronic drive. The biggest challenge to drive this experiment, to comprehend the MATLAB/SIMULINK simulation design and characteristic of each function block in Toolbox.